Mobile augmented reality for Bukit Brown cemetery navigation - Newton, Owen Noel (2013)
This paper presents the use of a mobile augmented reality for navigation and visualization of Bukit Brown Cemetery (BBC). Natural feature tracking is used to recognize each tombstone to eliminate the need of physical modifications to each grave. GPS-based terrain clustering techniques is applied to reduce the computation time and cost which overcomes linear search of whole natural feature data set against each video frame. The system will be used to visualize the heritage value of the cemetery and preserve important information about each tombstone in BBC.